Analisis ketidakpastian pengukuran pada mistar ingsut rentang 0-30 cm - I Gede Putu Agus Suryawan; I Gusti Komang Dwijana (Jurnal Energi Dan Manufaktur, 2006)
In science of measurement, an error is defined as difference result of measurement and the real value of the measurand.Actually, this real value is never precisely identified; consequently, the error is unknowns as well. In this case, the error canonly be estimated without knowing its real quantity. If a value will be considered as an estimated error, this value should be taken as an uncertainty. Uncertainty of Vernier Calliper determined with Type A and Type B evaluation, then the combinedstandard uncertainty is determined. Vernier Calliper that calibrated with Gauge Block class 1, the maximum uncertainty is ± 3.27 µm in dimension of 12.7 mm, with 95% confidence level.